2019
DOI: 10.22161/ijaers.610.12
|View full text |Cite
|
Sign up to set email alerts
|

In vitro control of Colletotrichum lindemuthianum by Trichoderma spp. and in vivo with Alternative Products

Abstract: Beans (Phaseolus vulgaris) are extremely important because it is included daily in the diet of themajority of the Brazilian population. Several factors negatively affect the productivity of this crop, especially diseases.One of the main ones is anthracnose (Colletotrichum lindemuthianum), which can cause total production damage and depreciation of the final product. The study and development of new strategies for integrated anthracnose management can reduce the cost of production and consequently reduce envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Gadaga et al (2017) and Hennipman et al (2019) reported lower anthracnose and angular spot severity with copper phosphite application on bean crops. However, Christmann et al (2019) and Assunção et al (2020) did not find the same result for anthracnose control in the same crop. )…”
Section: Discussionmentioning
confidence: 84%
“…Gadaga et al (2017) and Hennipman et al (2019) reported lower anthracnose and angular spot severity with copper phosphite application on bean crops. However, Christmann et al (2019) and Assunção et al (2020) did not find the same result for anthracnose control in the same crop. )…”
Section: Discussionmentioning
confidence: 84%
“…Any preventative resistance induction can generate metabolic or other costs which might result in negative effects on seed yield under enemy-free conditions, or when other environmental factors than the particular disease limit seed yield [ 62 ]. Evidently, such costs are likely to pay off if they protect the plant from a yield-limiting disease [ 63 , 64 , 65 ]. Indeed, inoculation of FMA bean seeds with each of the Trichoderma strains had a negative effect on seed yield in the anthracnose-free plot, but not so in the presence of anthracnose.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only one study reported a delay of anthracnose symptoms in the leaves of P. vulgaris after seed inoculation with T. viride or T. tomentosum and thereby shows that—in principle— Trichoderma spp. can trigger systemic resistance to C. lindemuthianum [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most used Cl control strategies are the use of resistant cultivars [107], the use of chemical controllers sprayed on the aerial part of the plant [108], seed treatment [109] and crop rotation [110]. Similarly, the use of biological control agents has been shown to be promising against Cl [111][112][113][114] and bacteria have played a prominent role in this approach [115,116].…”
Section: Discussionmentioning
confidence: 99%